Epigenetics, ethics, law and society: A multidisciplinary review of descriptive, instrumental, dialectical and reflexive analyses - Charles Dupras; Katie M. Saulnier; Yann Joly (2019)
Epigenetics, defined as ‘the study of mitotically and/or meiotically heritable changes in gene function that cannot be explained by changes in DNA sequence’, has emerged as a promissory yet controversial field of scientific inquiry over the past decade. Scholars from many disciplines have formulated both optimistic and cautionary claims regarding its potential normative implications. This article provides a comprehensive review of the nascent literature at the crossroads of epigenetics, ethics, law and society. It describes nine emerging areas of discussion, relating to (1) the impact of epigenetics on the nature versus nurture dualism, (2) the potential resulting biologization of the social, (3) the meaning of epigenetics for public health, its potential influence on (4) reproduction and parenting, (5) political theory and (6) legal proceedings, and concerns regarding (7) stigmatization and discrimination, (8) privacy protection and (9) knowledge translation. While there is some degree of similarity between the nature and content of these areas and the abundant literature on ethical, legal and social issues in genetics, the potential implications of epigenetics ought not be conflated with the latter. Critical studies on epigenetics are emerging within a separate space of bioethical and biopolitical investigations and claims, with scholars from various epistemological standpoints utilizing distinct yet complementary analytical approaches.